A brief review of applied psychology in China. Issue 1 (18th February 2022) - Wang, Richu; Han, Buxin; Zhang, Kan
Abstract: Psychology in China has a long past, but a rather short history. Modern psychology was introduced to China in the early 20th century soon, psychology as a scientific discipline was established when the teaching, research, and academic exchanges began. Specifically, applied psychology was established until the last decade of the 20th century; however, the past 30 years have witnessed the fast growth of applied psychology in China. In this article, we briefly introduce the history of psychology in China, its establishment as a discipline and a profession, and present some applications of psychology in the domains of public mental health as well as in educational and organizational settings.